The Nursing professional before the process of death and dying of the patient in the end of life (Research, Society and Development, 2020)
Death and dying are inevitable events and their possibilities can be present from birth to old age. However, nursing professionals have limitations to provide the necessary assistance to patients in the final stage of life and their families. The goal is to know, through scientific productions, the performance of nursing professionals before the patient in the final stage of life in the process of dying and dying. This is a narrative review in which the search for articles was carried out in April 2020 through access to the Virtual Health Library. The results obtained were discussed through categories: the ethical dilemmas regarding the death and dying process; spirituality and feelings experienced by the nursing team; and nursing skills and care in the final stage of life. It is considered that the adversities experienced by nursing professionals can be overcome based on spirituality and by the introduction of discussions on the topic still in the training process, through the understanding and acceptance of the finitude of life and the introduction of care palliative care for patients out of the possibility of cure and who will inevitably evolve to end-of-life care.